Chopped Strand/Plain Weave E-Glass as Reinforcement in Vacuum Bagged Epoxy Composites. (13th September 2015) - Heckadka, Srinivas Shenoy; Nayak, Suhas Yeshwant; Narang, Karan; Vardhan Pant, Kirti
Abstract : Polymer matrix composites are one of the materials being extensively researched and are gaining a lot of importance due to advantages like high specific strength, greater flexibility in design, and reduced cost of manufacturing. In this study, tensile, flexural, impact, and interlaminar shear strength of chopped strand/plain weave E-glass composites were considered. Composite laminates with different stacking sequence were fabricated using Vacuum Assisted Resin Infusion Moulding (VARIM) technique. Fiber volume fractions (FVF) of 22%, 26%, and 30% were adopted. Experiments were conducted in accordance with ASTM standards. Results indicate that laminates with three layers of plain weave mat exhibited better tensile, flexural, and interlaminar shear strength. However, laminates with two layers of chopped strand mat and one layer of plain weave mat showed improved impact resistance. In addition, scanning electron microscopy was used to analyze the fracture surface.